Online mobile content innovations and industry structure: implications for firms' strategies - Said, Mohd Fuaad; Adham, Khairul Akmaliah (Faculty of Economics and Management, Universiti Putra Malaysia, 2010)
Research literature indicates that successful market penetration and development using new technologies require technology entrepreneurs and managers to implement strategies that take advantage and overcome problems associated with important business environmental and product-specific factors. Using a conceptual framework drawn from important constructs in the Porter's competitive forces model and innovation literature, this study examines the Malaysian mobile content innovations and industry structure with the objective of understanding the variables that influence profitability of mobile content firms. To achieve the study's objective, extensive content analysis on all 43 Malaysian online mobile content firms' websites that were in operation in August 2008 was conducted and information on their innovations and industry structure from public domain were gathered. The study findings reveal important variables and linkages within, as well as those between, online mobile content firms' innovations and their industry contexts. These provide the basis for generating strategic propositions for the development of online mobile content firms as well as the overall mobile telecommunications industry. The study also concludes that deciding on the primary target market (PTM) is a critical consideration in mobile content business. Similarly important is for the mobile content firms, to evolve into transacting business entities, which activities will benefit all players in the mobile telecommunications service industry value chain.